Regarding the state of cybercrime prevention in Ukraine: problems of formation of official statistics - Havlovskyi, Vladyslav; Kovalchuk, Alla; Cherniavska, Bogdana (ScienceRise: Juridical Science, 2023)
The article analyzes the types, forms, and content of statistical reporting reflecting the state and structure of cybercrime in Ukraine. It is noted that there is currently no clear definition of the concept of cybercrime in domestic legislation. Among scientists and practitioners, there is also no single approach to delineating the grounds for classifying illegal acts as such crimes. At the same time, such uncertainty has a negative impact on the effectiveness of countering cybercrime in Ukraine. The purpose of the article is a systematic analysis of available state statistical data related to cybercrime, persons who have committed cybercrime, and other data reflected in various sources; an assessment of the structure and content of such data and the possibilities of their use for the prevention and counteraction of cybercrime; coverage of problematic issues related to the formation of official statistical reporting on recorded cybercrimes. On the basis of official state statistical reporting prepared by the Office of the Prosecutor General of Ukraine and the State Judicial Administration of Ukraine, it is possible to analyze a small group of criminal offenses, namely, those provided for by the articles of Chapter XVI of the Criminal Code of Ukraine. Some of the «traditional crimes» that fall under the concept of cybercrime are reflected in the departmental statistical reporting of the National Police of Ukraine, but it does not cover all cybercrimes and, of course, takes into account only those that are under the jurisdiction of the National Police of Ukraine. It was concluded that there is no official state statistical reporting on cybercrime in Ukraine. Considering the high latency of this type of criminal offense, it can be stated that it is impossible to conduct an analysis that would fully and reliably reflect the state of cybercrime in Ukraine